2021
DOI: 10.3390/ijms23010364
|View full text |Cite
|
Sign up to set email alerts
|

Anorexigenic Effects of Intermittent Hypoxia on the Gut—Brain Axis in Sleep Apnea Syndrome

Abstract: Sleep apnea syndrome (SAS) is a breathing disorder characterized by recurrent episodes of upper-airway collapse, resulting in intermittent hypoxia (IH) during sleep. Experimental studies with animals and cellular models have indicated that IH leads to attenuation of glucose-induced insulin secretion from pancreatic β cells and to enhancement of insulin resistance in peripheral tissues and cells, such as the liver (hepatocytes), adipose tissue (adipocytes), and skeletal muscles (myocytes), both of which could l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 110 publications
0
1
0
Order By: Relevance
“…OSAS is the most common. Multiple regression analysis has confirmed that SAS is a risk factor for unstable angina pectoris and myocardial infarction, but there is still a lack of large-scale clinical studies in China [ 5 ]. The occurrence of OSA is as high as 40% to 80% in patients with hypertension, coronary artery disease, heart failure, and pulmonary hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…OSAS is the most common. Multiple regression analysis has confirmed that SAS is a risk factor for unstable angina pectoris and myocardial infarction, but there is still a lack of large-scale clinical studies in China [ 5 ]. The occurrence of OSA is as high as 40% to 80% in patients with hypertension, coronary artery disease, heart failure, and pulmonary hypertension.…”
Section: Introductionmentioning
confidence: 99%